Covid-19 Aftermath of Higher Education in Bangladesh: A Shift Towards Hybrid Course Delivery - Faeique, Azmaine; Roza, Meherin Ahmed; Abdullah, Mohammad Tahmeed (Indonesian Journal of Education and Social Sciences, 2025)
COVID-19 brought a massive shift to the teaching and learning practices in higher education in Bangladesh. Although many universities in Bangladesh have started hybrid education, including both online and offline education styles, many students still need help with this hybrid process. The study aimed to evaluate the modifications made to teaching and learning strategies due to COVID-19 and to find the prospect of a shift towards Hybrid course delivery in higher education in Bangladesh. The study followed a quantitative method where the data collection was done through a close ended questionnaire using multistage sampling consisting of both stratified and simple random sampling. Students from 20 universities, whether public or private participated in this study. The study stratified the data with 20 responses per university and analysed 400 responses. The data was analysed using SPSS software for descriptive statistics, cross tabulation and chi square test. By conducting the Chi-square test (p> 0.05), the overall results of the study revealed that the universities conducting online classes, exams during the pandemic or not have no significant impact on the students preferring a hybrid course delivery. This is because the wave of digitalization has spread and made students accustomed to online education, courses and teaching platforms making them believe that Hybrid course delivery is a unique opportunity to combine the best aspects of both in-person and online learning, address the limitations of traditional classroom models, is cost effective and more flexible. The findings of this study will assist addressing the existing research vacuum in this field and help policymakers, administrators, educators, academicians, University Grant Commission (UGC) authorities, related ministries, and university authorities to rethink the process of Higher Education in Bangladesh.